Implementation of Conservation Management in Brantas River to be Red Bader Education Tourism - Daroini, Ahsin; Murdiyanto, Edi (Prosiding Seminar; 2020: 2020 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.37, 2020)
The purpose of this study examine the strengths, weaknesses, opportunities and threats or SWOT3 method in the effort to apply conservation management in Brantas River. The method used qualitative descriptive using SWOT analysis as a medium. Data collection: interviews, observation techniques and documentation. Research results of the study produced a strength and opportunities strategy matrix, a weakness and opportunities strategy, a weakness and threat strategy. The implementing conservation management had been educating the concept of educational tourism so that it is expected to educate the public in the use of rivers to be useful.